Convergence in the EU - Annette Bongardt; Francisco Torres; Pierre Wunsch; Carsten Hefeker; Christoph Hermann (Intereconomics, 2013)
The EU has long viewed economic and institutional convergence as important goals, but the results thus far have been decidedly mixed, and there remain several open questions: How exactly should convergence be defined? How much convergence is necessary? What steps can be taken to improve convergence in the EU, and how can success be defined? Finally, how much convergence can be achieved by improving the economic performance in underperforming regions, and how can convergence in the form of harmonisation towards lower welfare levels be avoided?
Keywords: 330